2017
DOI: 10.1080/00071668.2017.1327703
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enhancing vitamin D status by 25-hydroxycholecalciferol supplementation, alone or in combination with calcium and phosphorus, on sternum mineralisation and breast meat quality in broilers

Abstract: 1. The aim of the present study was to examine the effects of improving vitamin D status in broiler diets by supplementary 25-hydroxycholecalciferol (25OHD), alone or in combination with calcium (Ca) and available phosphorus (aP), on live performance, sternum mineralisation and breast meat quality in broilers. 2. A total of 936 1-d-old Ross 308 broilers were used in the study. After gender determination at the hatchery, chicks from each sex were randomly distributed into three dietary treatments. The following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
1
12
1
Order By: Relevance
“…The vitamin D source did not alter the performance of birds in the different evaluated periods. Bozkurt et al (2017) also did not observe improvement in WG at 10, 24, and 38 days when they used 25-OH-D 3 as a vitamin D source. Contrary to what was observed in this experiment, Yarger et al (1995) and Fritts and Waldroup (2003) found that the use of 25-OH-D 3 provided an increase in WG of broiler chickens.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The vitamin D source did not alter the performance of birds in the different evaluated periods. Bozkurt et al (2017) also did not observe improvement in WG at 10, 24, and 38 days when they used 25-OH-D 3 as a vitamin D source. Contrary to what was observed in this experiment, Yarger et al (1995) and Fritts and Waldroup (2003) found that the use of 25-OH-D 3 provided an increase in WG of broiler chickens.…”
Section: Discussionmentioning
confidence: 78%
“…On the other hand, the fact that rations present reduced Ca levels may have prevented interaction with P in the gastrointestinal tract, which would reduce the availability of this mineral as observed by Plumstead et al (2008). However, vitamin D 3 increased serum P levels in comparison with 25-OH-D 3 , contrary to the results observed by Bozkurt et al (2017). Studies have suggested that the effects of 25-OH-D 3 on dietary P use (Applegate et al, 2003) are not entirely clear .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Vitamin D is highly involved in both intestinal and uterine calcium transport, therefore 1,25(OH) 2 D markedly fluctuates with the ovulatory cycle of birds [166,167]. Consequently, dietary supplementation of vitamin D is vital and supplementation with 25(OH)D3 has shown some benefits over supplementation with vitamin D3 [168], including increased cellular immune response, improved mineral deposition in bones of broilers [169] and improved sternum structure and mineral accretion [170]. Hutton et al (2014) have demonstrated that supplementation with 25(OH)D3 improves breast meat yield in broilers by stimulating skeletal muscle satellite cells [171].…”
Section: Poultrymentioning
confidence: 99%